Impairment of PARK14-dependent Ca2+ signalling is a novel determinant of Parkinson’s disease - Qingde Zhou (Nature Portfolio, 2016)
PLA2g6 regulates store-operated Ca2+ entry and is linked to Parkinson’s disease. Here, Zhou et al find faulty PLA2g6-dependent Ca2+signaling in idiopathic PD patients, and show that its impairment triggers autophagic dysfunction and loss of dopaminergic neurons in a new PLA2g6 ex2KO mouse model.